Enhancing teacher professionalism through academic supervision: A CIPP model evaluation - Khofifah, Juliani Musti; Nurdin, Diding; Herawan, Endang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study evaluates the effectiveness of academic supervision practices at SMP Darul Hikam using the Context, Input, Process, and Product (CIPP) model. The urgency of this evaluation lies in the need to ensure that academic supervision evolves from a procedural obligation into a strategic mechanism for improving teacher professionalism and educational quality. Data were gathered through in-depth interviews, document analysis, and non-participatory observation. The research instruments were developed thematically based on the CIPP dimensions and validated through triangulation, member checking, and audit trail to ensure trustworthiness. The data were analyzed using thematic descriptive techniques aligned with the four CIPP components, with success criteria referring to national education standards, relevant policy frameworks, stakeholder satisfaction, and alignment with Taqwa Character Building (TCB) values. The results show that supervision at Darul Hikam is conducted systematically, supported by digital platforms (SISFO and Balanced Scorecard), and integrated into the school’s reflective and value-based culture. This approach has enhanced teacher competencies, fostered a culture of quality that is sustainable, and positively impacted student learning outcomes. The study concludes that academic supervision, when implemented through contextual leadership and technological integration, can serve as a transformative tool for professional development and institutional excellence.